Math, asked by galacticpearls20, 10 months ago

Solve the following: a) 3(2y + 3) - 4y + 3 b) 3 (y + 1) = 4y - 21 c) 3(y + 2) =2(y + 4) d) 5y - 6) = 4(y - 7) e) 2(3b - 4) = 5(b + 6) f) 3(2c + 5) = 4(c-3) g) 9(2d + 7) = 11 (d + 14) h) 5(7f - 3) = 28(f - 1)

Answers

Answered by koteswararao9
0

Answer:

{a}. \:  \:  \:  \:  2(3y + 4)

{b}. \:  \:  \:  y = 24

c. \:  \:  \:  y = 2

d. \:  \:  \: y = 2

e. \:  \:  \: b = 14

f. \:  \:  \: c =  -   \frac{27}{2}

g. \:  \:  \: d = 13

h. \:  \:  \:  \frac{43}{7}

Step-by-step explanation:

Plz Brainlist mark

Similar questions